Earnings Management Thresholds: The Case in Tunisia - Anis Ben Amar; Ezzeddine Abaoub (Asian Academy of Management Journal of Accounting and Finance, 2010)
Degeorge, Patel and Zeckhauser (1999) show that companies willingly manage their earnings with the aim of meeting or exceeding three earnings targets: zero earnings, last period’s earnings, and analysts' earnings forecasts. In this paper, we focus on earnings management designed to achieve the above earnings thresholds within the framework of the Tunisian market. Applying Burgstahler and Dichev’s (1997) methodology type to the annual data corresponding to the period from 1997 to 2004, our results indicate that Tunisian companies managed earnings to avoid losses and earnings decreases rather than to avoid negative earnings surprises.